2017
DOI: 10.5152/eurjther.2017.24
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of left atrial volume and function in neurocardiogenic syncope

Abstract: Objective:In this study, we aimed to investigate the presence of atrial volume and decrease in contraction force by measuring left atrial volume and contraction with the head-up tilt table (HUTT) test in patients who were diagnosed with neurocardiogenic syncope (NCS). Methods: Overall, 45 patients (26 females/19 males, mean age: 26.4±9.2 years) who experienced vasovagal syncope in HUTT (HUTT+) and 40 healthy controls (17 females/23 males, mean age:28.8±10.5 years; HUTT-) were included in the study. Results: Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Previous research has demonstrated a drop in mxLAV in patients with VVS and HUTT+. 5,7 We, however, not only demonstrated reduced mxLAV in VVS but also showed differences in miLAV and pre-P LAV between VVS groups with HUTT+ and HUTT− and the control group.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Previous research has demonstrated a drop in mxLAV in patients with VVS and HUTT+. 5,7 We, however, not only demonstrated reduced mxLAV in VVS but also showed differences in miLAV and pre-P LAV between VVS groups with HUTT+ and HUTT− and the control group.…”
Section: Discussionmentioning
confidence: 66%
“…Sucu et al 10 Başanalan et al 7 (2017) evaluated the LA ejection force, a marker derived from the mitral office area and the A wave, in patients with VVS and found that the force was lessened in patients with HUTT+ compared with those with HUTT−. They also reported that the LA ejection force was influenced by geometrical assumptions regarding Abbreviations: HUTT−, negative head-up tilt test; HUTT+, positive head-up tilt test; LA, left atrium; LAScd, left atrial longitudinal strain during the conduit phase; LASct, left atrial longitudinal strain during the contraction phase; LASr, left atrial longitudinal strain during the reservoir phase; pLASRcd, peak left atrial longitudinal strain rate during the conduit phase, pLASRct, peak left atrial longitudinal strain rate during the contraction phase; pLASRr, peak left atrial longitudinal strain rate during the reservoir phase; VVS, vasovagal syncope.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations